Immunofluorescence profile of discoid lupus erythematosus - Shreekant Bharti; Sunil Dogra; Biman Saikia; Ranjana Minz Walker; Seema Chhabra; Uma Nahar Saikia (Wolters Kluwer Medknow Publications, 2015)
The direct immunofluorescence (DIF) of skin in conjunction with histopathology gives the best diagnostic yield. It is invaluable in confirming the diagnosis of small vessel vasculitides and bullous lesions of the skin and can be used as an additional tool to pinpoint the diagnosis of systemic and localized autoimmune diseases involving the skin. This study was undertaken to analyze the strength of DIF vis-à -vis histopathology in the diagnosis of discoid lupus erythematosus (DLE) and at the same time to elaborate the specific immunofluorescence findings in the lesions of DLE. The clinical profile and cutaneous lesions of 75 patients with DLE are described. DIF was positive in 68% and histopathology in 60% of cases. The most common immunoreactant was IgG at the dermoepidermal junction, followed by IgM and IgA. A conclusive diagnosis of DLE could be achieved satisfactorily in 64 cases (85%) by a combination of the two techniques.